Adaptability of the Prospective of IPB Cayenne Pepper Varieties (Capsicum frutescens L.) in South Sumatra Tidal Lands - Karlin Agustina; E Mareza; Yursida Yursida; M Syukur; A Maharijaya (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
Adaptability of the prospective of IPB cayenne pepper varieties in tidal lands of South Sumatra was carried out from July 2020 to February 2021 in Banyu Urip Village, Tanjung Lago Subdistrict, Banyuasin District, South Sumatra. The research aimed to obtain prospective varieties that potential to be developed in tidal lands. The test used a Randomized Block Design with 3 replications. The treatment consisted of 5 prospective varieties of IPB cayenne pepper (F10-145291-10-7-1- 1-2-1-3B, F11-145291-115-15-8-1-1-2-5-3B, F11-160291-3-12-5-51-1-1-2-2-B, F8-145291-14-9-3-12- 1B, F10-145174-9-71-5-3-1-2B) and 5 commercial varieties (Harita, Gennie, Bara, Lentera, Baskara) as comparing varieties. Chilli was planted on a plot of 3 m x 5 m with a spacing of 60 cm x 70 cm. The analysis of variance used the F test and the HSD follow-up test. Prospective varieties of IPB cayenne pepper F8-145291-14-9-3-12-1B, F11-160291-3-12-5-51-1-1-2-2-B and F10-145291-10-7-1-1-2-1-3B had the potential to be developed in tidal lands of South Sumatra with respective productivity of 7.89 t/ha, 7.82 t/ha and 7.21 t/ha.